Analisis Laporan Keuangan Syariah : Studi Kasus Laporan Keuangan Bank Indonesia Syariah Tahun 2021-2023 - Agrayi Afifa Putri; Farhan Zulfahmi; Reina Reina; Ersi Sisdianto (Jurnal Riset Akuntansi, 2024)
Financial report analysis is closely related to the field of accounting. Financial report analysis basically aims to evaluate a company's financial reports with the aim of gaining an understanding of the company's future financial condition and performance. Sharia Bank is a financial institution that operates based on Islamic economic principles. PT. Bank Syariah Indonesia., Tbk (BSI) is a large company operating in the sharia financial industry and has an economic system based on Islamic law. In the research, a qualitative descriptive analysis method was used by displaying the financial report records of PT. Bank Syariah Indonesia (BSI) from 2021 to 2023.